2014
DOI: 10.1519/jsc.0b013e318297143a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Range of Motion During Ecologically Valid Resistance Training Protocols on Muscle Size, Subcutaneous Fat, and Strength

Abstract: The impact of using different resistance training (RT) kinematics, which therefore alters RT mechanics, and their subsequent effect on adaptations remain largely unreported. The aim of this study was to identify the differences to training at a longer (LR) compared with a shorter (SR) range of motion (ROM) and the time course of any changes during detraining. Recreationally active participants in LR (aged 19 ± 2.6 years; n = 8) and SR (aged 19 ± 3.4 years; n = 8) groups undertook 8 weeks of RT and 4 weeks of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 49 publications
11
99
2
Order By: Relevance
“…This suggests that resistance training can induce an increase in fascicle length of human muscles in vivo. In the 2000s, some studies showed an increase in fascicle length following resistance or competitive training [43][44][45][46][47][48][49][50][51][52][53] . Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) .…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that resistance training can induce an increase in fascicle length of human muscles in vivo. In the 2000s, some studies showed an increase in fascicle length following resistance or competitive training [43][44][45][46][47][48][49][50][51][52][53] . Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) .…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 99%
“…McMahon et al 48) showed a substantial impact of range of motion of the knee joint (i.e., muscle length change) during training on VL fascicle length change. They demonstrated that fascicle length of VL increased after resistance training for 8 weeks regardless of range of motion, but the magnitude was greater at longer range of motion (0° to 90°) than at shorter range of motion (0° to 50°) conditions.…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 99%
See 1 more Smart Citation
“…Full range of motion has been associated with greater strength and muscle gains [42][43][44]. In this context, the LP and 45LP can be considered superior to the other exercises with regard to conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…One of those, strength, is "Strength is the ability to apply force" [2] and the ability of muscles to cope with load or resistances. Meanwhile, strength level is influenced by some conditions: the length and size of muscles [13], the distance of load and fulcrum, the level of fatigue [14], the dominance of red and white muscle, muscle potential, the utilization of muscle, technique, and muscle contraction ability.…”
Section: Introductionmentioning
confidence: 99%